2016
DOI: 10.1080/00131881.2015.1129114
|View full text |Cite
|
Sign up to set email alerts
|

School policies on bullying and cyberbullying: perspectives across three Australian states

Abstract: BackgroundDespite decades of research, bullying in all its forms is still a significant problem within schools in Australia, as it is internationally. Anti-bullying policies and guidelines are thought to be one strategy as part of a whole school approach to reduce bullying. However, although Australian schools are required to have these policies, their effectiveness is not clear. As policies and guidelines about bullying and cyberbullying are developed within education departments, this paper explores the pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 35 publications
0
35
0
2
Order By: Relevance
“…Bullying is traditionally defined as repeated aggression or harmful actions directed at target individuals, who are disadvantaged or less powerful in their interactions with the perpetrator or the perpetrators (e.g. Chalmers et al 2016;Cowie and Jennifer 2008;Eriksen 2018;Espelage and Swearer 2011;Jimerson, Swearer, and Espelage 2010;Yang and Salmivalli 2015), even though there is an ongoing debate among scholars about how to define bullying (e.g. Canty et al 2016;Horton 2011;Schott and Søndergaard 2014;Volk, Veenstra, and Espelage 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bullying is traditionally defined as repeated aggression or harmful actions directed at target individuals, who are disadvantaged or less powerful in their interactions with the perpetrator or the perpetrators (e.g. Chalmers et al 2016;Cowie and Jennifer 2008;Eriksen 2018;Espelage and Swearer 2011;Jimerson, Swearer, and Espelage 2010;Yang and Salmivalli 2015), even though there is an ongoing debate among scholars about how to define bullying (e.g. Canty et al 2016;Horton 2011;Schott and Søndergaard 2014;Volk, Veenstra, and Espelage 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Also, policy-makers were interviewed about the definitions of school bullying and cyberbullying that they have used in their state policy frameworks. Most of the participants' definitions of bullying and cyberbullying in school context did not correspond fully with the commonly agreed definition used by researchers showing partial definition for bullying and/or cyberbullying in the area of repetition and intention without mentions of power imbalance (Chalmers et al, 2016).…”
Section: Introductionmentioning
confidence: 78%
“…Whichever way it is defined, bullying is a serious and widespread problem that severely affects those exposed to it at the time of the bullying (Cornell et al 2013;Rigby 2003) and has a long-term impact on their mental health and well-being (Arseneault, Bowes, and Shakoor 2010;Lereya et al 2015). Therefore, school staff and students need to know what bullying is in order to recognise, report, and stop it (Chalmers et al 2016; DeOrnellas and Spurgin 2017). Exclusion, talking about other people behind their backs, and spreading rumours about others, often called 'indirect bullying', tend not to be included as often in the lay bullying definitions (Maunder, Harrop, and Tattersall 2010) or in younger children's definition of bullying (Smith, Madsen, and Moody 1999).…”
Section: The Importance Of Defining Bullyingmentioning
confidence: 99%
“…Several studies have found that teachers experience difficulties in applying the definition of bullying (Ellwood and Davies 2010;Migliaccio 2015;Naylor et al 2006) and that they spend much time and effort on determining whether an incident is bullying (Allen 2015). Educators' definitions of bullying often differ from the definition commonly used by researchers (Chalmers et al 2016;Cheng et al 2011;Craig, Bell, and Leschied 2011;Harger 2016); likewise, staff and students' definitions also frequently differ (Maunder, Harrop, and Tattersall 2010;Naylor et al 2006). Many studies have found that students may construct and justify bullying victimisation as a consequence of the 'victim's' perceived difference from themselves (Forsberg 2017;Ryan and Morgan 2011;Thornberg 2011Thornberg , 2015.…”
Section: The Bullying Definition In Practicementioning
confidence: 99%
See 1 more Smart Citation